TANTANGAN GLOBALISASI DI TENGAH BERTUMBUHNYA PROGRAM STUDI PGSD UNIVERSITAS PGRI PALEMBANG (TINJAUAN FILSAFAT PENDIDIKAN PAULO FREIRE) - Dedy, Adrianus (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2018)
Globalization accompanied by rapid advances in technology and information brings great influence in all aspects of life, including aspects of education. In essence education aims to humanize humans. In reality, the influence of globalization in the form of modern capitalist structures seeks to color the world of education today is market and commercial. The impact is the pattern of college education, including PGRI University of Palembang in general and the PGSD study program in particular, may lose its identity as the basis of academic-scientific activities. To refine the essence of education amid the plight of commercial conditions, Paulo Freire's thoughts are an inspiration for the provision of quality higher education. Paulo Freire's thought is an educational function aimed at humanizing human beings in the midst of oppressive social structures. To that end, the task of education has a dual function, namely to increase critical awareness and transform social structures that oppress